Direitos humanos e esporte: como o “Caso George Floyd” ajudou a transformar regras do jogo - Melo, Andrei Schmidt Kampff de (2023)
The "George Floyd case" provoked a series of events in civil society and also in sport. The main one, a collective and spontaneous mobilization that provoked irritation in the sports organization. It was questioning the protection of human rights and freedom of expression within the sporting environment. The pressure provoked by sponsors, global collectives and by the athletes themselves against discrimination triggered major debates and changes within the legal organization of sport. The historic sports “neutrality” was challenged based on universal human rights banners and the very nature of sport. This dissertation reflects on sports autonomy, sports organization and the legal chain of sport, from the perspective of permanent guidelines for the protection of human rights that sport needs to be aware of. From the reflection of thinkers of law and freedom, decisions of state and private courts of sport and the presentation of numerous reports on the subject, advance in the paths that sport needs to take to protect its essence, with athletes as protagonists of this debate. The text show how the organized participation of athletes in the defense of human rights transforms not only the reality of sport, but also helps in building a better world